Chapter A Rhetorical Model of Debating - Llano, Stephen M. (Communication and Philosophical Cultures. Researches and Instruments, 2021)
A rhetorical model of the debate centered on the image of a labyrinth is more suitable than the metaphor of debate-as-game in describing the benefits of arguing in front of an audience. The labyrinth best expresses that proceeding by successive choices, coming and going, and sometimes retracing one's steps, typical of the debate activity. The basic thesis is that arguing is a continuous adaptation of one's speeches according to the audience that listens. In fact, in the labyrinth, what matters is not only arriving at the outcome - the exit or reaching the center of the structure - but the path you choose to get there is equally important. More than the definitive and winning argument, which rarely occurs in discussions, the labyrinth teaches us to recognise the plurality of approaches adopted when faced with an issue.